Microstructure and mechanical properties of doped and electron-beam treated surface of hypereutectic Al-11.1%Si alloy - Dmitrii Zaguliaev; Sergey Konovalov; Yurii Ivanov; Victor Gromov; Elizaveta Petrikova (Journal of Materials Research and Technology, 2019)
The effect of electroexplosive doping in two modes with subsequent intense pulsed electron beam treatment of hypereutectic Al-11.1%Si alloy (silumin) on the change of its structure and phase composition, mechanical and tribological properties has been investigated. Methods of methods of scanning electron microscopy, electron microprobe and X-ray diffraction analysis were used to analyze changes of the structure, phase composition, and morphology of the modified surface of hypoeutectic silumin subjected to a complex treatment. Change of tribological and mechanical properties after the complex energy deposition is evaluated: the microhardness increases by 3.2 times (2.34 GPa in contrast to 0.73 GPa in the as-cast state), the wear parameter (inverse to the wear resistance) decreases by 18–20 times (from 49⋅10−4 mm3/N⋅m to 2.5⋅10−4 mm3/N⋅m) and the friction coefficient decreases by ≈1.5 times (from 0.55 to 0.36). It is revealed that a complex treatment mode hardly affects the studied properties but it has a strong effect on the phase composition of a modified layer (the content of the aluminum-based solid solution is reduced by 2.5 times, and the relative content of silicon oxide grows by ≈2.2 times). The multiphase submicro- and nanocrystalline structure formed in the surface layer is responsible for changes in the wear resistance and microhardness, and special features of the thermal action by an intense pulsed electron beam on the surface govern a decrease in the friction coefficient. Keywords: Al-Si hypereutectic alloy, Electron beam, Electroexplosive doping, Microstructure, Wear resistance, Microhardness